REVITALISASI GLODOK SEBAGAI TEMPAT BERSOSIALISASI KOMUNITAS MASYARAKAT TIONGHOA - Sharen Sharen; Budi Adelar Sukada (Jurusan Arsitektur dan Perencanaan, 2020)
Glodok Pancoran is one of the areas in DKI Jakarta that has high economic and cultural values in the Netherlands, colonizing Indonesia until now. Glodok Pancoran, known as the center of typical Chinese and Betawi trade, ranging from culinary, medicine, and trinkets has great potential as an area of art and cultural tourism in West Jakarta. This research describes the development planning of the Glodok Pancoran to improve the image of the region and maximize the potential of the arts and cultural tourism. The pattern of trading life and daily activities become the basis for designing the design with the aim to increase Jakarta or foreign tourists. Data analysis was performed using theory, namely analysis based on environmental aspects, human aspects and building aspects combined with other theories. The result that will be received is the design concept of the Glodok Pancoran area as an art and cultural tourism area in West Jakarta by taking into account tourism experiences within the area. The result that will be achieved is the design concept Glodok Pancoran area as an art and cultural tourism area in Pinangsia village, West Jakarta by taking into account the experience of tourists in the area. Keywords: Art and Culture Tourism; Glodok Pancoran; Pecinan Abstrak Kawasan Glodok Pancoran merupakan salah satu kawasan di DKI Jakarta yang memiliki nilai ekonomi dan budaya yang tinggi. Kawasan Glodok telah eksis sejak jaman Belanda menjajah Indonesia sampai saat ini. Glodok Pancoran yang dikenal sebagai pusat perdagangan khas Tionghoa dan Betawi, mulai dari kuliner, obat-obatan, dan pernak-pernik mempunyai potensi yang besar sebagai kawasan wisata seni dan budaya di Jakarta Barat. Studi ini menjelaskan tentang perencanaan perkembangan kawasan Glodok untuk meningkatkan citra kawasan dan memaksimalkan potensi wisata seni dan budaya. Pola kehidupan berdagang dan aktivitas sehari-hari menjadi dasar untuk perancangan desain dengan tujuan untuk meningkatkan wisatawan kota Jakarta maupun mancanegara. Analisis data dilakukan dengan menggunakan teori yaitu analisis berdasarkan aspek lingkungan, aspek manusia dan aspek bangunan yang dipadu dengan teori lainnya. Hasil yang akan dicapai adalah konsep desain kawasan Glodok Pancoran sebagai kawasan wisata seni dan budaya di kelurahan Pinangsia, Jakarta Barat dengan memperhatikan pengalaman wisatawan di dalam kawasan.